Effects of a green tea extract, Polyphenon E, on systemic biomarkers of growth factor signalling in women with hormone receptor‐negative breast cancer. Issue 3 (19th March 2014) - Crew, K. D.; Ho, K. A.; Brown, P.; Greenlee, H.; Bevers, T. B.; Arun, B.; Sneige, N.; Hudis, C.; McArthur, H. L.; Chang, J.; Rimawi, M.; Cornelison, T. L.; et al.
Abstract Background Observational and experimental data support a potential breast cancer chemopreventive effect of green tea. Methods We conducted an ancillary study using archived blood/urine from a phase IB randomised, placebo‐controlled dose escalation trial of an oral green tea extract, Polyphenon E (Poly E), in breast cancer patients. Using an adaptive trial design, women with stage I–III breast cancer who completed adjuvant treatment were randomised to Poly E 400 mg (n = 16), 600 mg (n = 11) and 800 mg (n = 3) twice daily or matching placebo (n = 10) for 6 months. Blood and urine collection occurred at baseline, and at 2, 4 and 6 months. Biological endpoints included growth factor [serum hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF)], lipid (serum cholesterol, triglycerides), oxidative damage and inflammatory biomarkers. Results From July 2007‐August 2009, 40 women were enrolled and 34 (26 Poly E, eight placebo) were evaluable for biomarker endpoints. At 2 months, the Poly E group (all dose levels combined) compared to placebo had a significant decrease in mean serum HGF levels (−12.7% versus +6.3%, P = 0.04). This trend persisted at 4 and 6 months but was no longer statistically significant. For the Poly E group, serum VEGF decreased by 11.5% at 2 months (P = 0.02) and 13.9% at 4 months (P = 0.05) but did not differ compared to placebo. At 2 months, there was a trend toward a decrease in serum cholesterol with Poly E (P = 0.08). No significant differences were observed for other biomarkers. Conclusions Our findings suggest potential mechanistic actions of tea polyphenols in growth factor signalling, angiogenesis and lipid metabolism.